PENGARUH MEKANISME CORPORATE GOVERNANCE DAN KARAKTERISTIK PERUSAHAAN TERHADAP KINERJA LINGKUNGAN - Yesika, Nina; Chariri, Anis (Diponegoro Journal of Accounting, 2013)
This research aims to determine the impact of corporate governance mechanism and corporate characteristics to environmental performance. The proxy of corporate governance mechanism is size of board commisioner, proportion independence of board commisioner, and audit committee meeting. The proxy of corporate characteristic is profitability, leverage, and variety industri. Environmental performance is measured by PROPER rating that issued by Environmental Ministry. Research design is quantitative method to determine the relationship between variables by testing hypothesis. The examined technique hypohesis is mutiple regression by using SPSS program. The result of research is proportion independence of board commisioner and variety of industry had positive significant influence otherwise size of board commisioner had negative significant influence on environmental performance. Profitability, leverage and audit committee meeting had no significant influence on environmental performance. The result was not appropriate with legitimacy theory that state profitability and leverage had a negative significant influence on environmental performance.